Expression of cyclin D1 in epithelial tissues of transgenic mice results in epidermal hyperproliferation and severe thymic hyperplasia. - Robles, A I (1996)
To study the involvement of cyclin D1 in epithelial growth and differentiation and its putative role as an oncogene in skin, transgenic mice were developed carrying the human cyclin D1 gene driven by a bovine keratin 5 promoter. As expected, all squamous epithelia including skin, oral mucosa, trachea, vaginal epithelium, and the epithelial compartment of the thymus expressed aberrant levels of cyclin D1. The rate of epidermal proliferation increased dramatically in transgenic mice, which also showed basal cell hyperplasia. However, epidermal differentiation was unaffected, as shown by normal growth arrest of newborn primary keratinocytes in response to high extracellular calcium. Moreover, an unexpected phenotype was observed in the thymus. Transgenic mice developed a severe thymic hyperplasia that caused premature death due to cardio-respiratory failure within 4 months of age. By 14 weeks, the thymi of transgenic mice increased in weight up to 40-fold, representing 10% of total body weight. The hyperplastic thymi had normal histology revealing a well-differentiated cortex and medulla, which supported an apparently normal T-cell developmental program based on the distribution of thymocyte subsets. These results suggest that proliferation and differentiation of epithelial cells are under independent genetic controls in these organs and that cyclin D1 can modulate epithelial proliferation without altering the initiation of differentiation programs. No spontaneous development of epithelial tumors or thymic lymphomas was perceived in transgenic mice during their first 8 months of life, although they continue under observation. This model provides in vivo evidence of the action of cyclin D1 as a pure mediator of proliferation in epithelial cells.